Preliminary reference values for Alzheimer’s disease plasma biomarkers in Congolese individuals with and without dementia - Ikanga, Jean; Jean, Kharine; Medina, Priscilla; Patel, Saranya Sundaram; Schwinne, Megan; Epenge, Emmanuel; Gikelekele, Guy; Tshengele, Nathan; Kavugho, Immaculee; Mampunza, Samuel; Mananga, Lelo; Teunissen, Charlotte E.; et al. (Frontiers in Aging Neuroscience, 2024)
BackgroundWestern countries have provided reference values (RV) for Alzheimer’s disease (AD) plasma biomarkers, but there are not available in Sub-Saharan African populations.ObjectiveWe provide preliminary RV for AD and other plasma biomarkers including amyloid-β (Aβ42/40), phosphorylated tau-181 and 217 (p-tau181, p-tau217), neurofilament light (Nfl), glial fibrillary acidic protein (GFAP), interleukin 1b and 10 (IL-1b and IL-10) and tumor necrosis factor α (TNFα) in Congolese adults with and without dementia.Methods85 adults (40 healthy and 45 dementia) over 50 years old were included. Blood samples were provided for plasma AD biomarkers Aβ42/40 and p-tau181, p-tau217; Nfl and GFAP; IL-1b and IL-10 and TNFα analyzed using SIMOA. Linear and logistic regressions were conducted to evaluate differences in biomarkers by age and gender and neurological status, and for the prediction of dementia status by each individual biomarker. RV were those that optimized sensitivity and specificity based on Youden’s index.ResultsIn this sample of 85 adults, 45 (53%) had dementia, 38 (45%) were male, overall mean age was 73.2 (SD 7.6) years with 8.3 (5.4) years of education. There were no significant differences in age, gender, and education based on neurological status. Biomarker concentrations did not significantly differ by age except for p-tau181 and GFAP and did not differ by sex. Preliminary normal value cutoffs of various plasma in pg./mL were 0.061 for Aβ42/40, 4.50 for p-tau 181, 0.008 for p-tau 217, 36.5 for Nfl, 176 for GFAP, 1.16 for TNFa, 0.011 for IL-1b, and 0.38 for IL-10. All AUCs ranged between 0.64–0.74. P-tau 217 [0.72 (95% CI: 0.59, 0.84)] followed by GFAP [0.72 (95% CI: 0.61, 0.83)], and Nfl [0.73 (95% CI: 0.62, 0.84)] had the highest AUC compared to other plasma biomarkers.ConclusionThis study provides RV which could be of preliminary utility to facilitate the screening, clinical diagnostic adjudication, and classification, of dementia in Congolese adults.